2023
DOI: 10.1101/2023.08.14.23294059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methodological development of molecular endotype discovery from synovial fluid of individuals with knee osteoarthritis: the STEpUP OA Consortium

Abstract: Objectives: To develop and validate a pipeline for quality controlled (QC) protein data for largescale analysis of synovial fluid (SF), using SomaLogic technology. Design: Knee SF and associated clinical data were from partner cohorts. SF samples were centrifuged, supernatants stored at -80oC, then analysed by SomaScan Discovery Plex V4.1 (>7000 SOMAmers/proteins). Setting: An international consortium of 9 academic and 8 commercial partners (STEpUP OA). Participants: 1746 SF samples from 1650 individuals co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…All participants gave written informed consent with local (institution specific) ethical approvals in place. Following the QC procedure, 1361 samples were identified from unique participants with established OA [27] . Individual cohorts were assigned, a priori , into Discovery (N = 708) and Replication (N = 653) datasets (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…All participants gave written informed consent with local (institution specific) ethical approvals in place. Following the QC procedure, 1361 samples were identified from unique participants with established OA [27] . Individual cohorts were assigned, a priori , into Discovery (N = 708) and Replication (N = 653) datasets (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…We have also previously shown that proteins regulated in knee OA or after knee injury, compared with healthy controls, are readily detected in the SF but correlate poorly in paired blood [2225] . Furthermore, we have previously confirmed the utility of high scale protein measurements in SF using the SomaScan® platform (SomaLogic, Inc, Boulder, Colorado), an aptamer-based assay [26, 27] . The SomaScan® platform V4.1 measures over 6596 distinct human proteins.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations